BUDIDAYA SAYURAN ORGANIK PADA PEKARANGAN RUMAH DI DESA WARI INO, KECAMATAN TOBELO - Kastanja, Ariance Yeane; Patty, Zeth; Kaboru, Rian Ritno (HIRONO : Jurnal Pengabdian Masyarakat, 2021)
Organic vegetable cultivation training was carried out for a group of housewives in Wari Ino village by utilizing their yards, with the outputs being the concept of empowerment and a yard cultivation model adopted by the community, especially housewives. The problem faced by members is the low utilization of their yards due to low knowledge and skills in cultivating organic vegetables. The method of implementing this activity is counseling, training on vegetable cultivation in the yard. The results obtained from this activity are the increased knowledge and skills of members in the use of yard land, and each member has used the land of the house by planting various types of vegetable plants.